Wybrane problemy z właściwą wykładnią umów prawa autorskiego - Skrzypczak, Jędrzej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
Recently, the increasing importance and the legal, as well as business and social, significance of copyright agreements has been noted in legal dealings. Given the growing range of such agreements one should not be surprised about the increasing problem of their correct interpretation. This paper attempts to present only some of the significant problems encountered in the process of the correct interpretation of such declarations of intent made by legal entities. In the light of practical experience it appears that the issues that are discussed in the paper should be considered with particular attention. The problems that usually arise are the consequence of negligence of the parties to such agreements. It should also be admitted, however, that another reason for problems may be rapid technical progress that legislation cannot always keep up with. Therefore, it has been necessary to review the most important opinions expressed in the doctrine and judicial decisions in this respect.